An incomplete information static game for the evaluation of the community based forest management in Zagros forests, Iran - Zandebasiri, M.; Filipe, J.; Soosani, J.; Pourhashemi, M.; Salvati, L.; Mata, M. N.; Mata, P. (Sustainability, 2020)
The present study adopts a game theory approach for analyzing land-use planning in Zagros forest, Iran, by applying a Static Game of Incomplete Information (SGII) to the evaluation of participatory management of forest landscape. This tool allows a complete evaluation of sustainable forest planning producing two modeling scenarios based on (i) high or (ii) low social acceptance. According to the SGII results, the Nash Bayesian Equilibrium (NBE) strategy demonstrates the importance of landscape protection in forest management. Results of the NBE analytical strategy show that landscape protection with barbed wires is the most used strategy in local forest management. Response of local community includes cooperation in high social acceptance condition and noncooperation in low social acceptance condition. Overall, social acceptance is an adaptive goal in forest management plans.